Pengaruh Penerapan Syariah Compliance Terhadap Kepuasan Nasabah PT. Bank Sumut KCPSy. Hamparan Perak - Saidah Saidah; Nurul Inayah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
In order to capture the attention and interest of customers, sharia banking in Indonesia is developing extremely quickly and becoming more competitive in the delivery of financial services. In order for banks to meet the difficulties of the industrial revolution, they must create and improve methods for figuring out what elements draw in clients and foster customer loyalty. Customer loyalty may be increased through relationship marketing, a positive corporate reputation, and adherence to sharia law. The goal of this study is to ascertain if the satisfaction variable may mediate the effect of compliance on customer loyalty at Bank Sumut KCP Syariah Hamparan Perak as well as the influence of compliance on customer loyalty. Utilizing a quantitative methodology, this investigation. The major information utilized in this study was collected by questionnaires utilizing a measuring scale, namely using a Likert scale. 101 participants made up the sample in this study. According to the findings of the experiments, customer loyalty is positively and insignificantly impacted by relationship marketing variables, company image, and consumer satisfaction, positively and significantly impacted by sharia compliance, and positively and significantly impacted by relationship marketing variables, company image, and sharia compliance. important for ensuring client happiness.